2014
DOI: 10.4236/ojpm.2014.48076
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes and Practices of Medical and Paramedical Staff in Blood Transfusion in the Democratic Republic of Congo

Abstract: Objective: To assess the knowledge, attitudes and practices of providers in blood transfusion, HIV infections and hepatitis B and C in the province of South Kivu (eastern DRC). Methods: This study is comparative cross-sectional. It covered all the staff care. Our sample was composed by doctors, nurses, midwives, and agents' rapid training in activity in health sector in South Kivu between 1 December 2011 and 30 December 2011. Those medical and paramedical staffs came from 12 general reference hospitals, 11 hos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
8
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 17 publications
5
8
1
Order By: Relevance
“…), this result was in the same line with Tetteh, 2015 (22) who found that nurses' had excellent Knowledge related to patient preparation about blood transfusion .In addition to Yaghoobi, et al,2014 (23) , who mentioned that more than half of studied sample had a good knowledge before blood transfusion…”
Section: Discussionsupporting
confidence: 78%
“…), this result was in the same line with Tetteh, 2015 (22) who found that nurses' had excellent Knowledge related to patient preparation about blood transfusion .In addition to Yaghoobi, et al,2014 (23) , who mentioned that more than half of studied sample had a good knowledge before blood transfusion…”
Section: Discussionsupporting
confidence: 78%
“…The proportion of subjects who received training in blood transfusion (22.2%) in our study is comparable to that (29.1%) recorded in Mali in 2010 [13] and the Democratic Republic of Congo in 2011 (25.5%) [17] in relatively similar surveys. Unlike Diakité et al [13] and similarly to Kabinda et al [17], the results of our study showed that the quality of responses was better among prescribers who received training in blood transfusion.…”
Section: Training In Blood Transfusion and Gendersupporting
confidence: 83%
“…Unlike Diakité et al [13] and similarly to Kabinda et al [17], the results of our study showed that the quality of responses was better among prescribers who received training in blood transfusion. Thus, as already shown by Tramalloni et al [18], transfusion practice in hospitals could be improved if training is widely provided/strengthened to blood prescribers.…”
Section: Training In Blood Transfusion and Gendercontrasting
confidence: 59%
See 1 more Smart Citation
“…The level of knowledge observed was globally low concerning blood safety and basics about blood-borne pathogens. 8 The aim of this study was to assess the level of knowledge, attitudes, and practices of HCW toward HBV and HCV in Bukavu, an eastern town of DRC.…”
Section: 6mentioning
confidence: 99%